PULMONARY EMBOLISM, THROMBOCYTOPENIA, AND ANTIPHOSPHOLIPID SYNDROME - Mahmud, Talha (Journal of Ayub Medical College Abbottabad, 2011)
This case report describes a young non-smoker male masquerading under the diagnosis of community acquired pneumonia who was found to have respiratory symptoms attributed to bilateral pulmonary emboli. There was also evidence of thrombocytopenia and proximal deep venous thrombosis of right lower limb. He underwent further investigations and was found to have positive anti-cardiolipin antibodies, lupus anticoagulant and prolonged activated partial thromboplastin time due to antiphospholipid antibody syndrome. This article highlights the importance of consideration of earlier diagnosis in younger patients with congenital thrombophilias that carries potential for prevention and treatment of life threatening thromboembolic manifestations. Keywords: Anti-phospholipid antibody syndrome, activated partial thromboplastin time, aPTT, deep venous thrombosis, pulmonary embolism, thrombocytopenia